THE NATURE AND FUNCTIONS OF SPECIALIZED DICTIONARIES IN MODERN LEXICOGRAPHY - Xudoyqulova Marjona; Mamarajabov Anvar; Tog’aymurodova Parizod (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Specialized dictionaries play a crucial role in modern lexicography by addressing the specific linguistic needs of particular fields such as medicine, law, technology, and education. Unlike general-purpose dictionaries, they focus on terminology, usage, and conceptual clarity within a defined domain. This article explores the nature, structure, and key functions of specialized dictionaries, highlighting their importance in academic, professional, and communicative contexts.